Can Risk-taking Preferences be Modified? Some Experimental Evidence - Alison L. Booth; Patrick J. Nolen (Center for Economic Studies and ifo Institute (CESifo), 2014)
We summarise our two sets of controlled experiments designed to see if single-sex classes within coeducational environments modify studentsf risk]taking attitudes. In Booth and Nolen (2012b), subjects are in years 10 and 11, while in Booth, Cardona]Sosa and Nolen (2014), they are first]year university students randomly assigned to single]sex and coed classes. While on average females are significantly less likely than men to make risky choices, on exposure to single]sex environments they behave the same as the males. Thus part of the observed gender difference in behavior under uncertainty found in previous studies might reflect social learning rather than inherent gender traits.
Keywords: C90; C91; C92; J16; D01; D80; J16; J24; 330; gender; risk preferences; single-sex groups; cognitive ability